Effect of General Anesthesia On Apgar Score In Relation To Induction-Delivery and Uterine-Delivery Interval - Ismaiel Mohammad, Saad (Tikrit Journal of Pharmaceutical Sciences, 2023)
The anaesthetic drugs technique used in caesarean section should prevent fetal depressant resulting from passing of drugs through the maternal-placental barrier which can lead to adverse effects such as decreasing in Apgar score and respiratory depression in new born neonates. Apgar score is the first test given to newborn after delivery by caesarian section or normal vaginal delivery to evaluate a newborn physical condition after delivery and to determine any immediate need for extra medical or emergency care. To determine the effect of general anaesthetic drugs on the Apgar score of new-borns in relation to the induction-delivery interval and uterine delivery interval. One hundred healthy full term pregnant women underwent elective C/S, on left lateral position the pre induction with 100% oxygen by face mask, then start induction with minimum dose of Thiopentone (3mg/kg ) with ketamine (1mg/kg), followed by non-depolarization muscle relaxant atracurium(0. 5 mg/kg ). Endotracheal intubation was done and maintenance of anaesthesia with oxygen, 0.5% Halothane and atracurium (0. 1 mg/kg) till the end of surgery. Neostigmine (2.5 mg) and atropine (1.2mg) was given as antidote. During operation the heart rates, blood pressures and oxygen saturation (pulse oxymeter) were monitored. Oxytocin (20 units) or ergometrine (0.8 mg) is injected intravenously after clamping the cord, then (tramadol 75 mg + midazolam 5mg) was given. Induction- delivery interval and uterine-delivery interval was noted using a stopwatch. After delivery the baby’s Apgar score was noted at 1, 5 and 10 min. and proper resuscitation was done. Low Apgar score and low to moderate score at one minute was found when induction –delivery interval up to five minutes and more than 10 minutes also low and low to moderate score of infants when uterine – delivery interval more than 120 seconds. One minute Apgar score of infants were affected by induction-delivery time (≤ 5 min and > 10 min) and uterine –delivery interval (>120 sec).